Genetic, epigenetic and genomic effects on variation of gene expression among grape varieties. (7th June 2019) - Magris, Gabriele; Di Gaspero, Gabriele; Marroni, Fabio; Zenoni, Sara; Tornielli, Giovanni Battista; Celii, Mirko; De Paoli, Emanuele; Pezzotti, Mario; Conte, Federica; Paci, Paola; Morgante, Michele
Summary: The transcriptional regulatory structure of plant genomes is still relatively unexplored, and little is known about factors that influence expression variation in plants. We used a genetic system consisting of 10 heterozygous grape varieties with high consanguinity and high haplotypic diversity to: (i) identify regions of haplotype sharing through whole‐genome resequencing and single‐nucleotide polymorphism (SNP) genotyping; (ii) analyse gene expression through RNA‐seq in four stages of berry development; and (iii) associate gene expression variation with genetic and epigenetic properties. We found that haplotype sharing in and around genes was positively correlated with similarity in expression and was negatively correlated with the fraction of differentially expressed genes. Genetic and epigenetic properties of the gene and the surrounding region showed significant effects on the extent of expression variation, with negative associations for the level of gene body methylation and mean expression level, and with positive associations for nucleotide diversity, structural diversity and ratio of non‐synonymous to synonymous nucleotide diversity. We also observed a spatial dependency of covariation of gene expression among varieties. These results highlight relevant roles for cis ‐acting factors, selective constraints and epigenetic features of the gene, and the regional context in which the gene is located, in the determination of expression variation. Open Research Badges: This article has earned an Open Data Badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available athttps://www.ncbi.nlm.nih.gov/bioproject/PRJNA385116 ;https://www.ncbi.nlm.nih.gov/bioproject/PRJNA392287 ;https://www.ncbi.nlm.nih.gov/bioproject/PRJNA373967 (released upon publication);https://www.ncbi.nlm.nih.gov/bioproject/PRJNA490160 (released upon publication);https://www.ncbi.nlm.nih.gov/bioproject/PRJNA265039 ;https://www.ncbi.nlm.nih.gov/bioproject/PRJNA265040 . Significance Statement: The transcriptional regulatory structure of plant genomes is still relatively unexplored in comparison with that of animals, and little is known about sequences that affect gene expression and about genetic and epigenetic factors that influence expression variation in plants. The combination of data of different types allowed us to identify relevant roles for gene body methylation, expression levels, structural and nucleotide diversity, selective constraints and gene richness, as well as local spatial effects on gene expression variation and covariation.